Effects of Kinesio taping on blood fatigue factors after isokinetic exercise - Ko, Y. J.; Kim, J. S. (Journal of Exercise Rehabilitation, 2021)
This study examined the effects of Kinesio taping on recovery from fatigue induced by an exercise of concentric contraction using an isokinetic machine. Eight healthy collegiate students participated in two experiments: the Kinesio taping application condition and the no Kinesio taping application condition. The fatigue was induced by concentric exercise at 60°/sec, 50 repetitions for one session, and repeated 3 sessions. Changes of blood ammonia, lactate, lactate dehydrogenase (LDH), and creatinine kinase (CK) were monitored. Blood was collected before exercise, immediately after exercise, 24 hr after exercise, and 72 hr after exercise. Blood ammonia tended to reduce during the recovery process, but no differences were found between conditions. Blood lactate tended to reduce during the recovery process, but no differences were found between conditions. In the blood LDH, no differences were found between conditions. Blood creatine kinase tended to reduce during the recovery process, but no differences were found between conditions. The present results showed that Kinesio taping did not affect the recovery phase of blood ammonia, lactate concentration, LDH, and CK.